2019
DOI: 10.1002/ecy.2569
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning wild bee and hoverfly contributions to plant–pollinator network structure in fragmented habitats

Abstract: The risk of ecosystem function degradation with biodiversity loss has emerged as a major scientific concern in recent years. Possible relationships between taxonomic diversity and magnitude and stability of ecosystem processes build upon species' functional characteristics, which determine both susceptibility to environmental change and contribution to ecosystem properties. The functional diversity within communities thus provides a potential buffer against environmental disturbance, especially for properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 60 publications
5
27
3
Order By: Relevance
“…Likely, the positive relationship between flower density and network specialization is due to resource partitioning 19,70,71 , as increases in flower availability might increase the possibilities of bumblebee species to focus on different resources to optimize foraging and avoid competition 15 . Our results regarding patch shape complexity are in the line of other studies that also found a negative relationship between network specialization and habitat loss or disturbance 23,26 . The reasons for a decrease in network specialization as patch shape complexity increases might be twofold.…”
Section: Discussionsupporting
confidence: 92%
“…Likely, the positive relationship between flower density and network specialization is due to resource partitioning 19,70,71 , as increases in flower availability might increase the possibilities of bumblebee species to focus on different resources to optimize foraging and avoid competition 15 . Our results regarding patch shape complexity are in the line of other studies that also found a negative relationship between network specialization and habitat loss or disturbance 23,26 . The reasons for a decrease in network specialization as patch shape complexity increases might be twofold.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 50% of the interactions in our plant-pollinator networks were dominated by syrphid flies and apid bees, which are highly mobile and utilize a variety of habitat types, indicating the insect pollinators in our observed networks may have traveled considerable distances to utilize the semi-natural reservoirs embedded within this cropland matrix. (Morris 1993;Sommaggio et al 1999;Beekman and Ratneiks 2000;Klecka et al 2018;Jauker et al 2019). These findings are also consistent with other studies such as Winfree et al (2007) and Hoehn et al (2008) demonstrating that landscapes dominated by intensive agriculture can still maintain relatively diverse pollinator communities provided patches of floral resources were present.…”
Section: Landscape Effects On Pollinator Diversitysupporting
confidence: 87%
“…Nevertheless, there is an alarming global decline of insect pollinators largely attributed to anthropogenic pressures such as land-use intensification and widespread use of pesticides (Kearns et al 1998;Steffan-Dewenter et al 2005). Given these documented declines, there is an increased interest in conserving pollinator communities and their habitats to stabilize these critical ecosystem services and in turn, ecosystem function (Steffan-Dewenter et al 2002;Kremen et al 2002;Olesen et al 2007;Peterson et al 2010;Redhead et al 2018;Jauker et al 2019).…”
Section: Body Of Article: Introductionmentioning
confidence: 99%
“…Numerous metrics at both the network and species level have been developed and can provide useful quantitative summaries of pollination network properties (Gibson et al, 2011;Jauker, et al, 2018). Proper interpretations of selected network parameters can help us to understand pollinators' responses to habitat alteration, biodiversity change, and climate change by comparing changes in interactions over time or across disturbance gradients (Proulx et al, 2005;Ballantyne et al, 2015;Bohan & Dumbrell, 2017).…”
Section: Introductionmentioning
confidence: 99%